LigA formulated in AS04 or Montanide ISA720VG induced superior immune response compared to alum, which correlated to protective efficacy in a hamster model of leptospirosis - Varma, Vivek P.; Kadivella, Mohammad; Kumar, Ajay; Kavela, Sridhar; Faisal, Syed M. (Frontiers in Immunology, 2022)
Leptospirosis is a zoonotic disease of global importance. The current vaccine provides serovar-specific and short-term immunity and does not prevent bacterial shedding in infected animals. Subunit vaccines based on surface proteins have shown to induce protection in an animal model. However, these proteins were tested with non-clinical adjuvants and induced low to moderate protective efficacy. We formulated a variable region of Leptospira Immunoglobulin-like protein A (LAV) in clinical adjuvants, AS04 and Montanide ISA720VG, and then evaluated the immune response in mice and protective efficacy in a hamster model. Our result shows that animals immunized with LAV-AS04 and LAV-Montanide ISA720VG (LAV-M) induced significantly higher levels of LAV-specific antibodies than LAV-Alum. While LAV-Alum induced Th2 response with induction of IgG1 and IL-4, AS04 and LAV-M induced a mixed Th1/Th2 response with significant levels of both IgG1/IL-4 and IgG2c/IFN-g. Both LAV-AS04 and LAV-M induced the generation of a significantly higher number of cytotoxic T cells (CTLs). The immune response in LAV-AS04 and LAV-M immunized animals were maintained for long period (>180 days) with the generation of a significant level of B and T cell memory. The strong immune response by both the vaccines correlated to enhanced recruitment and activation of innate immune cells particularly DCs at draining lymph nodes and formation of germinal centers (GCs). Further, the immune response generated in mice correlated to protective efficacy in the hamster model of Leptospirosis. These results indicate that LAV-AS04 and LAV-M are promising vaccines and can be further evaluated in clinical trials.